2022
DOI: 10.2196/33929
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based mHealth Intervention With Telephone Support to Increase Physical Activity Among Pregnant Patients With Overweight or Obesity: Feasibility Randomized Controlled Trial

Abstract: Background Pregnant patients with overweight or obesity are at high risk for perinatal complications. Excess gestational weight gain (GWG) further exacerbates this risk. Mobile health (mHealth) lifestyle interventions that leverage technology to facilitate self-monitoring and provide just-in-time feedback may motivate behavior change to reduce excess GWG, reduce intervention costs, and increase scalability by improving access. Objective This study aimed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In addition, there were also some articles discussed about short-massage service applications, mHealth technology [12], [19], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], Telemedicine [3], [20], [32], [33], [34], the use of applications [35], [36], [37], MyFitnessPal phone app [23], Mi Fit app [38], e-Moms Roc [16], WhatsApp social application [39], [40], SEESPA [41], RapidSMS [42], E screening [43], [44], PEARS [28], [45], and Cellular-enabled glucometers [46]. Others were about watch-based applications and video conferencing like using a smartwatch [47], Telehealth: video conference [45], [48], [49], flexible maternity virtual ward services [50], internet-based [24], [51], website Williamson [52], and Text or voice message [53].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were also some articles discussed about short-massage service applications, mHealth technology [12], [19], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], Telemedicine [3], [20], [32], [33], [34], the use of applications [35], [36], [37], MyFitnessPal phone app [23], Mi Fit app [38], e-Moms Roc [16], WhatsApp social application [39], [40], SEESPA [41], RapidSMS [42], E screening [43], [44], PEARS [28], [45], and Cellular-enabled glucometers [46]. Others were about watch-based applications and video conferencing like using a smartwatch [47], Telehealth: video conference [45], [48], [49], flexible maternity virtual ward services [50], internet-based [24], [51], website Williamson [52], and Text or voice message [53].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 39 RCTs, 18 (46%) had published results on GWG outcomes. Of these 18 RCTs, 8 (44%) were pilot RCTs [41,42,105,109,125,127,139,140], and 10 (56%) were efficacy or effectiveness RCTs [39,99,103,111,115,118,120,134,138,141]. Significant intervention effects on any GWG outcome were found in 7 (39%) of these 18 studies [39,103,115,118,120,127,134], whereas 11 (61%) observed no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 67 (69%) reports from the database and trial register searches together with 15 (15%) eligible reports identified via internet search and 15 (15%) eligible reports identified by citation searching, amounting to a total of 97 reports from 43 studies, were included in this scoping review. Of the 97 included reports, 38 (39%) were TREs , 49 (50%) were full peer-reviewed articles [25,26,[38][39][40][41][42], 5 (5%) were conference abstracts [133][134][135][136][137], 2 (2%) were preprints [138,139], 1 (1%) was a master's thesis [140], 1 (1%) was a dissertation [141], and 1 (1%) was a grant report [142].…”
Section: Study Selection and Sources Of Evidencementioning
confidence: 99%
“…The decision to omit a weight monitoring feature and focus on healthy eating and PA rather than GWG-related messaging was based on the comments by participants, in particular those who had experienced difficulty with their weight, that weight messages were demotivating and a potential barrier to engagement. This approach contrasts with that of other existing digital interventions that aim to promote healthy eating and PA and prevent excessive GWG in pregnancy [ 25 , 44 , 45 ]. The extent to which weight monitoring contributes to the effectiveness of multifaceted digital interventions is unclear.…”
Section: Discussionmentioning
confidence: 99%